Analysis of Passenger Satisfaction Level of Service And Facilities of Electric Rail Train (KRL) Commuter Line Route Bekasi - Manggarai - Rifai, Andri Irfan; Fajriliani, Yuditami Iressa (Journal of World Conference (JWC), 2020)
The train is considered to act as strategic public transport because of its ability to reduce congestion in urban areas. Various modes of transportation are in a race - a race to improve the quality of service that requires rail freight also needs to improve in all areas. Service is the main priority which is used as a benchmark in competitive advantages and facilities are factors that affect the services provided by the transport company. This is the underlying researchers to conduct research on passenger satisfaction ratings on the level of service performance and service facilities Commuter Line KRL Bekasi - Manggarai and to determine the factors affecting passenger satisfaction. Data obtained in the form of a survey by questionnaire online delivery methods. Methods of data analysis software used isms. Excel and SPSS software for statistical testing. The conclusions of the research by the method of Customer Satisfaction Index (CSI) obtained a passenger satisfaction index score of 76.11%. It is stated that the passengers very satisfied with the performance of services and facilities service station Commuter Line KRL Bekasi - Manggarai, only for the suitability of the train arrival and departure needs to be improved.